PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATERI POLA BILANGAN DI KELAS VIII SMP NEGERI 3 WERTAMRIAN KABUPATEN KEPULAUAN TANIMBAR - Mesak Ratuanik; Blasius Lolonlun; Zakarias Bacori (JURNAL EDUSCIENCE, 2022)
This study aims to determine the learning design of speech pattern material for class VIII students of SMP Negeri 3 Wertamrrian using a problem based learning model and determine students' ability to understand mathematical concepts through number patterns after using a problem-based learning model for class VIII students of SMP Negeri 3 Wertamrrian. This research was conducted at SMP Negeri 3 Wertamrian, Tanimbar Islands Regency in November 2022. This type of research is a qualitative research using a research design. Data collection methods used are research documentation, written tests and interviews. The data analysis technique used is data reduction, data presentation and conclusions or verification. The results of the study design research using a problem based learning (PBL) model on Bialngan Pattern material in class VIII of SMP Negeri 3 Wertamrian are as follows: (a) In the first and second meeting learning, the researcher reviewed the material related to the learning objectives to be achieved. (b) The researcher gave 2 problems to students, namely 1 problem at the first meeting and 1 problem at the second meeting. Then ask students to check the sentences or questions contained in the problem that they have not understood. (c) Researchers divide students into groups to solve problems. (d) Researchers assist students in solving the problems given by providing the supports that have been provided in the HLT that the researchers designed. (e) Researchers provide opportunities for group representatives to present each problem that has been discussed. (f) Researchers together with students discuss and check the results of the discussions that have been presented and evaluate the learning process that occurs. (2) The ability to understand mathematical concepts of class VIII SMP Negeri 3 Wertamrian on number pattern material after following the mathematics learning process using PBL is as follows: (a) In problem 1, students have a more dominant concept understanding ability in indicators 1, 3 and 4, namely restating each concept, presenting the concept in various forms of mathematical representation and using, utilizing and selecting certain procedures or operations in solving problems. (b) In problem 2, students have more dominant concept understanding skills in indicators 1, 3 and 4, namely restating each concept, presenting concepts in various forms of mathematical representation and using, utilizing, and choosing certain procedures or operations in solving problems.